Neo-imperialism fact or fancy? - Castro, Amado A. (1971)
The purpose of this paper is to examine the thesis expounded so forcefully by Mr. Alejandro Lichauco in a recent work entitled, Imperialism and the Security of the State. I propose to present my discussion in the following order: first, I will examine briefly the theory of imperialism, especially as it is presented in its most effective form today, as part of Marxist-Leninist thought. Then I will look at Mr. Lichauco's paper itself, and finally, I will put forward some reflections of my own on the subject.
Keywords: Imperialism; Criticism; Lichauco, Alejandro -- Criticism and interpretation